Sustainable biorefining of woody biomass to biofuels and biochemicals - Kumar, Deepak; Kumar, Sachin; Rajendran, Karthik (Applied biotechnology reviews series, 2024)
Sustainable Biorefining of Woody Biomass to Biofuels and Biochemicals explores various technologies and pathways for the valorization of woody biomass to produce sustainable biofuels and bioproducts. Focusing on commercialization, the book discusses woody biomass availability, including harvesting, transportation and storage, biomass structure, advanced biorefinery technologies, and the economic and environmental sustainability of woody biomass-based biorefineries. Various technologies are described and assessed from a commercial perspective and practical solutions to the latest challenges are provided. The last section of the book is dedicated to the commercialization aspects of biorefineries, providing details about the techno-economic viability and environmental impact of various biorefinery approaches.This book provides readers with a unique and comprehensive reference that will help students and researchers alike identify and overcome the challenges involved in woody-biomass biorefining for biofuels and biochemicals. It will also be of interest to researchers and professionals involved more broadly in bioenergy and renewable energy, and interdisciplinary teams working across biotechnology, chemistry and chemical engineering, environmental science, and plant sciences